Probabilistic thinking, characteristic features - Szitányi, Judit (Teaching Mathematics and Computer Science, 2012)
This paper is the first step in a series of a general research project on possible development in probability approach. Our goal is to check with quantitative methods how correct our presumptions formulated during our teaching experience were. In order to get an answer to this question, we conducted a survey among third-year students at our college about their general and scientific concepts as well as about the way they typically think.